Private Speech as a Form of Self-Regulation in Managing Speaking Anxiety among EFL University Students - Nawal Maulida, Nimas Ayu; Azzahra, Farla Syifa; Rafif Yumna, Mochammad Alfat; Pamungkas, Damar Jati; Koesoemo Ratih; Endang Fauziati (Samudra Publisher, 2026)
This study examined how non-English major university students in Indonesia use private speech as a self-regulatory strategy for managing English speaking anxiety. Using a qualitative descriptive design, eight second-semester students from three universities were selected through purposive sampling and completed an open-ended online survey; responses were analyzed using six-phase thematic analysis. Findings identified five types of private speech self-encouragement, self-instruction, self-evaluation, cognitive reframing, and religious self-talk used mainly before speaking tasks, functioning as both emotion-focused and problem-focused coping that generally reduced anxiety and increased readiness to speak. However, perceived effectiveness varied across participants, indicating that private speech operates as a conditional rather than universal coping resource, with effects on self-efficacy shaped by prior speaking experience. These findings extend understanding of self-regulation among non-English major EFL learners and offer preliminary implications for raising student awareness of internal coping strategies and informing anxiety-sensitive speaking instruction.